2020
DOI: 10.1371/journal.pone.0232168
|View full text |Cite
|
Sign up to set email alerts
|

Not sick enough to worry? "Influenza-like" symptoms and work-related behavior among healthcare workers and other professionals: Results of a global survey

Abstract: Background Healthcare workers (HCWs) and non-HCWs may contribute to the transmission of influenza-like illness (ILI) to colleagues and susceptible patients by working while sick (presenteeism). The present study aimed to explore the views and behavior of HCWs and non-HCWs towards the phenomenon of working while experiencing ILI. Methods The study was a cross-sectional online survey conducted between October 2018 and January 2019 to explore sickness presenteeism and the behaviour of HCWs and non-HCWs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 29 publications
2
65
2
1
Order By: Relevance
“…sore throat, nasal discharge, etc.) who would still go to work is higher (89–99%) [ 29 ]. This also seems true for COVID-19; a report of HCWs screened during an outbreak in a LTCF in the US showed that 64.6% of HCWs with confirmed SARS-CoV-2 infection worked while they were symptomatic, and for a median duration of 2 days (range 1–10) [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…sore throat, nasal discharge, etc.) who would still go to work is higher (89–99%) [ 29 ]. This also seems true for COVID-19; a report of HCWs screened during an outbreak in a LTCF in the US showed that 64.6% of HCWs with confirmed SARS-CoV-2 infection worked while they were symptomatic, and for a median duration of 2 days (range 1–10) [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…This will require significant cultural change. A global survey on sickness presenteeism comparing the self-reported behavior of health care workers and non-healthcare workers with influenza like illness found that the majority of both groups would continue to work, despite health care workers knowing the risks of transmitting influenza-like illness to vulnerable patients (62). Possible reasons for sickness presenteeism included understaffing, a sense of obligation to colleagues, and economic reasons such as lack of sick leave -all of which exist in veterinary settings.…”
Section: What Can Veterinary Teams Do To Prepare For Ethical Challenges?mentioning
confidence: 99%
“…Occupational testing first became available to symptomatic HCW at Liverpool University Hospitals NHS Foundation Trust on 2 nd April 2020. However, presenteeism in HCW may be a contributory factor, even in the context of a global respiratory pandemic (Tartari et al, 2020). Clarification on and reinforcement of self-isolation and testing policies for HCW when symptomatic is advisable, especially given symptomatic infections are likely more transmissible (Buitrago-Garcia et al, 2020).…”
Section: Discussionmentioning
confidence: 99%